The Maqashid Shariah in Priority Banking Strategy: An Analysis of Bank Syariah Indonesia Gorontalo Branch - Muhammad Syarif H Djauhari; Supandi Rahman (Department of Islamic Banking, 2025)
Purpose – This study aims to analyze the application of maqashid syariah principles in marketing strategies carried out by Priority Banking Officers (PBOs) at Bank Syariah Indonesia (BSI) Gorontalo branch office. In an era of tight competition, marketing strategies based on sharia principles are an important key to attracting and retaining priority customers. Methodology – This study uses a qualitative approach by interviewing PBOs and analyzing related documents to explore how Maqashid Syariah is implemented in banking services. Findings – The results of the study indicate that BSI Gorontalo has implemented several strategies in accordance with maqashid sharia, such as a personal approach to customers, exclusive services based on justice and welfare, and investment education in accordance with sharia principles. These strategies aim to improve the social welfare of customers, as well as ensure the sustainability and growth of the bank. Implications – These findings indicate that the implementation of maqashid sharia not only strengthens the bank's position in the sharia banking market, but also has a positive impact on community welfare. Originality – Therefore, further research is expected to explore how this strategy can be expanded and optimized to achieve a greater social impact in society.